ANALISIS KUALITAS AIR TANAH DAERAH TERDAMPAK ROB SEBAGAI UPAYA UNTUK MENDAPATKAN SUMBER AIR BERSIH DAN MENANGGULANGI PENURUNAN TANAH - Maghfiroh Maghfiroh; Mutadin Mutadin (LPPM Universitas Pekalongan, 2021)
Seawater eruption disasters has an impact on changes in the concentration of groundwater chemical species. This can affect the quality of groundwater which is commonly used as a source of clean water. The concentration of chemical species in groundwater determines whether the water is suitable for consumption by the community. The eligibility is based on the Regulation of the Minister of Health of the Republic of Indonesia No. 492/Menkes/Per/IV/2010. The quality of groundwater was seen from the parameters of pH, chloride ion concentration, sulfate ion concentration, and water hardness. Analysis of pH was measured by the SNI 6989.11: 2019 method (using a pH meter), analysis of chloride ions and sodium ions using SNI 6989.19: 2009 (argentometry), and salinity analysis. The results of this study indicate that tidal inundation and distance from the sea affect the quality of groundwater in Wonokerto, Pekalongan. Well water in all villages in Wonokerto qualified the environmental health quality standards and water health requirements for sanitation hygiene purposes, but not all of them qualified the requirements for drinking water according to Indonesian health minister regulations.